COVID-19 InfoVaccines: A WHO-supported educational project to promote COVID-19 vaccination information among professionals and the general population - Narmeen Mallah; Jacobo Pardo-Seco; Irene Rivero-Calle; Ouhao Zhu-Huang; María Fernández Prada; Catharina Reynen-de Kat; Oleg Benes; Liudmila Mosina; Siddhartha Sankar-Datta; Olga Aleksinskaya; David Díaz; Vusala Allahverdiyeva; et al. (Human Vaccines & Immunotherapeutics)
COVID-19 vaccine uptake varied across countries, in part due to vaccine hesitancy fueled by a lack of trustworthy information. To help health workers provide evidence-based answers to common questions about COVID-19 vaccines and vaccination, and thereby, assist individuals´ decisions on vaccine acceptance, COVID-19 InfoVaccines, a joint WHO-EU project, was launched in February 2021 to support COVID-19 vaccine rollout in 6 Eastern European countries. COVID-19 InfoVaccines was made available in seven languages and shared on social media networks. A total of 262,592 users accessed COVID-19 InfoVaccines.com between February 11, 2021, and January 31st, 2023. The users were most interested in: general questions; vaccine efficacy and duration of protection; vaccine safety; vaccine co-administration, and dose-interval and interchangeability; though the interest in a specific theme varied in function of the epidemiological situation. A total of 118,510 (45.1%) and 46,644 (17.7%) users scrolled up to 35% and 75% of the COVID-19 InfoVaccines webpage, respectively. The average engagement rate was 71.61%. The users accessed COVID-19 InfoVaccines from 231 countries and territories, but the majority were in Ukraine (N = 38,404; 14.6%), Spain (N = 23,327; 8.9%), and Argentina (N = 21,167; 8.1%). Older Facebook users were more interested in COVID-19 information than younger individuals (X2 p-value < .0001). Two hundred twenty-eight videos were shared on YouTube. The average Click-Through-Rate on Facebook was 7.82%, and that on YouTube was 4.4%, with 60 videos having a Click-Through-Rate >5%, falling in the range of average YouTube video Click-Through-Rate (2% – 10%). As misinformation about vaccines and vaccination spreads easily and can negatively impact health-related decisions, initiatives like COVID-19 InfoVaccines are crucial to facilitate access to reliable information.